2011
DOI: 10.1103/physreva.84.041601
|View full text |Cite
|
Sign up to set email alerts
|

Expansion dynamics of the Fulde-Ferrell-Larkin-Ovchinnikov state

Abstract: We consider a two-component Fermi gas in the presence of spin imbalance, modeling the system in terms of a one-dimensional attractive Hubbard Hamiltonian initially in the presence of a confining trap potential. With the aid of the time-evolving block decimation method, we investigate the dynamics of the initial state when the trap is switched off. We show that the dynamics of a gas initially in the Fulde-Ferrel-Larkin-Ovchinnikov (FFLO) state is decomposed into the independent expansion of two fluids, namely t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 32 publications
6
43
0
Order By: Relevance
“…A recent experiment [12] has realized a spin-imbalanced Fermi gas in an array of 1D systems and has demonstrated that the observed density profiles are in agreement with theoretical predictions [13][14][15]. An actual experimental proof of the presence of a spatially modulated quasicondensate in this system, expected from theory [16][17][18][19][20][21], is still lacking, which has led to a large number of proposals for schemes to probe FFLO correlations [22][23][24][25][26][27]. Many of these proposals involve the presence of an optical lattice along the 1D direction, suggesting that the Fermi-Hubbard model is the appropriate model.…”
Section: Introductionmentioning
confidence: 77%
“…A recent experiment [12] has realized a spin-imbalanced Fermi gas in an array of 1D systems and has demonstrated that the observed density profiles are in agreement with theoretical predictions [13][14][15]. An actual experimental proof of the presence of a spatially modulated quasicondensate in this system, expected from theory [16][17][18][19][20][21], is still lacking, which has led to a large number of proposals for schemes to probe FFLO correlations [22][23][24][25][26][27]. Many of these proposals involve the presence of an optical lattice along the 1D direction, suggesting that the Fermi-Hubbard model is the appropriate model.…”
Section: Introductionmentioning
confidence: 77%
“…[63]. In their experiment, Papp et al studied a 85 Rb Bose-Einstein condensate, which is a strongly interacting bosonic superfluid. Traditionally, experimental studies of bosonic superfluids have been carried out on liquid helium, but a gas of Bose-condensed atoms has the advantage that the interparticle interactions can be tuned via Feshbach resonance.…”
Section: Summary Of Publication Imentioning
confidence: 99%
“…For this reasons the imbalanced systems has been studied vigorously -both theoretically and experimentally. Theoretical studies on imbalanced systems often focus on the possibility of exploring imbalanced superconducting states in different JHEP01 (2014)136 physical systems, for example, in population-imbalanced Ultracold atomic gases [38,[40][41][42], optical lattices [43], heavy-fermionic superconductor CeCoIn 5 [44], two-dimensional organic superconductors [37,39,45,46] and quark matter core of the neutron stars [47,48]. The experimental search is a topic of vigorous research till date as it is very hard to pinpoint this state in the phase diagram.…”
Section: Condensed Matter Descriptionmentioning
confidence: 99%